Characterization of Silver Nanoparticle Electrolysis Method with UV-Vis Spectrometer, Atomic Absorption Spectrophotometer, and Particle Size Analyzer - Latumakulita, Ivandra Immanuela; Suparno, Suparno (Kasuari: Physics Education Journal (KPEJ), 2022)
This work reports the production and characteristics of silver nanoparticles by electrolysis method at different voltages and electrolysis time with respect to their soluble concentration. This research is an experimental research. The research sample was the result of a solution of silver nanoparticles by the electrolysis method. The purpose of this research was to determine the effect of electrolysis voltage on the concentration of silver nanoparticles, the effect of electrolysis time on the concentration of silver nanoparticles, and characterization using UV-Vis, AAS and PSA. In this research there are two stages, namely the production stage and the characterization stage. The production of silver nanoparticles was carried out using 99% AgBr rods and aquades by electrolysis method. Characterization was carried out by testing on UV-Vis, AAS and PSA spectrometers to determine light absorption, ionic silver concentration and silver nanoparticle size. The results of this research indicate that the greater the electrolysis voltage and time, the higher the concentration of the solution obtained. The concentrations obtained at each voltage were 38 ppm, 42 ppm and 54 ppm. Characterization using UV-VIS spectrometer showed that the silver nanoparticle solution at each concentration was able to absorb light at wavelengths of 419.50 nm, 442 nm and 431 nm with absorbance peaks of 1,158, 2,989, and 0.904. Characterization using AAS showed that the content of silver nanoparticles in solution at each concentration were 8.7 ppm, 15 ppm and 17 ppm. Characterization using PSA showed that the solution at each concentration had silver nanoparticle sizes were 110.7 nm, 209.2 nm, 175.2 nm.